Semicontinuous Emulsion Copolymerization of Vinyl acetate and Butyl acrylate with Nonionic Surfactants (Triton X Series) - Karacetin, Gulsum; Sarac, Ayfer (WILEY-V C H VERLAG GMBH, 2015)
In this study, the copolymerization of vinyl acetate (VAc) and butyl acrylate (BuA) in water semicontinuous emulsions made with the nonionic surfactants, Triton Xs, was studied as a function number of ethylene oxide (EO, X) and their concentrations. The copolymerization of VAc and BuA was initiated by peroxide at proper temperature in order to improve the efficiency of droplet nucleation and maintain the stability of the emulsion. The effects of EO's in the surfactant structure and surfactant concentration on latex colloidal and physicochemical properties were investigated.
Keywords: ethylene oxide; latexes; stability; surfactant; PARTICLE-SIZE DISTRIBUTION; POLYMERIZATION; STYRENE; METHACRYLATE; X-100; Polymer Science